Development and Design Of 8x1 Micro Strip Antenna Array for Military/Satellite Communication - Mary Joy Kinol, A.; Sahaya Anselin nisha, A. (International Journal of Engineering and Technology, 2018)
Antenna design has become as established field of research in recent years. The most important feature of MPA is low cost, low profile and single layer configuration. The frequency band at which the patch antenna operates is 12-1GHz and antenna array are fielded by Microstrip field line incorporated with 50 Ω impedance. In order to achieve enhancement in gain, directivity, bandwidth and return loss Quarter wave transformer and power divider are used. Microstrip patch antenna, employed with highly reflective properties   is presented with the results of modeling, design and simulation. To illustrate this techniques a KU band 2×1, 4×1, 8×1antenna array integrated with series corporate feeding network are designed and simulated. The maximum gain of14.56dB at 10 GHz, the impedance beam width is 86.72% and 99% efficiency is arrived using this technique. Maximum radiation pattern is achieved by using low dielectric substrate of RT-DURROID. The design is verified using HFSS software, used to simulate the antenna array.